Stylistic in children's stories - Wulandari; Helmanto, Fachri; Rosnawati (LADU: Journal of Languages and Education, 2024)
Background:  Stylistics examines the use of language that assesses aesthetics in children's stories. It requires stylistics to bind readers by presenting interesting stories and arousing curiosity. In contrast, stylistics in children's stories can be found if the stylistic devices are known. Purpose: The purpose of this study is to explore stylistics in children stories of five graders in SDN Kompa Design and methods: This type of research uses qualitative with a literature review method. The literature selection technique uses keywords story, device, and stylistics. Results: This study identifies various stylistic devices, such as Parallelism, Chiasmus, Antithesis, Climax, Asyndeton, Sentential adverb, Irony, Understatement, Litotes, Hyperbole, Metabasis, Hypophora, Distinction, Metanoia, Zeugma, Diazeugma, Mesozeugma, Hypozeugma, Syllepsis, Hyperbaton, Anastrophe, Appositive, Simile, Metaphor, Chatachresis, Metonymy, Personification, Apostrophe, Transferred epithet, Anaphora, Epistrophe, Simploce, Anadiplosis, Conduplication, Epanalepsis, Diacope, Epizeuxis, Scesis Onomaton, Alliteration, Onomatopoeia, Assonance, Rhetorical question, Apophesis, Anacoluthon, Oxymoron, and Antimetabole, used in children's short stories to enhance narrative appeal and expression.